Innovative and energy efficient algorithm for heating and cooling systems control based in thermal comfort standards - Batista, Gilberto (2012)
This paper presents the development of an innovative and energy efficient algorithm for Heating, Ventilating, Air Conditioning and Refrigeration (HVAC-R) systems control based in thermal comfort standards. Most of the actual control of these systems is done by thermostats that measure only the air temperature but don’t take into account the air humidity neither the occupant’s individual parameters like their activity and clothing. Thus, these systems require frequent adjustment of thermostats set-point in order to promote thermal comfort to the occupants. This paper presents a control algorithm that uses as set-point, not the air temperature, but the Predicted Mean Vote (PMV) index, which is defined by the thermal comfort ISO 7730:2005 standard and depends on more parameters than just the air temperature. Thus, it provides a more efficient control and greater comfort to the occupants. Besides this innovative aspect concerning the control algorithm, another one is related to the wireless and energy harvesting sensors and actuators that can be used to provide much more flexibility and energy autonomy.